Solitary osteoma of body of the mandible - Saba Khan; Laxmikanth Chatra; K Prashanth Shenai; Sreeja P Kumar (Wolters Kluwer Medknow Publications, 2013)
Osteomas are relatively rare benign osteogenic neoplasm's characterized by the proliferation of compact or cancellous bone. Osteomas can develop as peripheral (periosteal) masses attached to the cortical plates or as central lesions arising from endosteal bone surfaces. Although multiple osteomas of the jaws are a hallmark of Gardner's syndrome (familial adenomatous polyposis), non-syndromic cases are typically solitary. The purpose of this paper is to present a large peripheral osteoma originating from the buccal surface of the mandible and causing asymmetry in a 35-year-old woman.